Using social media in the classroom : a best practice guide - Poore, Megan (SAGE, 2016)
'A book for every teacher's bookshelf. This book gives a comprehensive overview of the tools and apps that can be used to help turn a mediocre teaching session into an outstanding one.' - Cheryl Hine, Leeds City College.